Wpływ stresu na życie rodziców dziecka z zaburzeniami ze spektrum autyzmu - BEDNÁROVÁ, LUCIA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Lucia Bednárová, The significance of stress in parents of a child with Autism Spectrum Disorders, Interdisciplinary Contexts of Special Pedagogy, No. 22, Poznań 2018. Pp. 121–132. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.07 The literature review focuses on the importance of stress in parents of a child with autism spectrum disorders, which significantly affects family life. The main cause of the burden are accompanying difficulties that are the part of disorder. This applies to specific reactions such as fits of anger, self-harm, psychomotor agitation, eating disorders, sleep disorders and other troubles which require almost 24-hour care. This review assesses several research studies that deal with the issue and which can be examples of good practice.